Answer:
x=-38
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
3(x−6)−2(2x+3)=14
(3)(x)+(3)(−6)+(−2)(2x)+(−2)(3)=14(Distribute)
3x+−18+−4x+−6=14
(3x+−4x)+(−18+−6)=14(Combine Like Terms)
−x+−24=14
−x−24=14
Step 2: Add 24 to both sides.
−x−24+24=14+24
−x=38
Step 3: Divide both sides by -1.
−x
−1
=
38
−1
x=−38
Answer:
it's 8-3m
Step-by-step explanation:
The 2 like terms are 400km +924m
Answer:
x=12.
Step-by-step explanation:
Let's get this straight out of the way, the 3 angles of a triangle ALWAYS add up to 180. Now that that's said, lets begin. Since the opposing side of an angle is the same as the regular side, we simplify to get: 5x+120=180. 180-120=60. so 5x=60. 60/5=12. so x=12.